2017
DOI: 10.1080/17429145.2017.1294712
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping patterns and different farming systems affect the yield and yield components of safflower and bitter vetch

Abstract: This factorial field experiment was done based on a randomized complete block design in Urmia University, Iran, in 2013 and was repeated in 2014. Treatments included two farming systems (high input and organic) and different intercropping patterns that alternated bitter vetch (Vicia ervilia L.) and safflower (Carthamus tinctorius L.) with row ratios of 2:2, 3:2, 4:2 and 5:2. Sole cropping of bitter vetch and safflower was used as the control. In both years, the 2:2 intercropping pattern had biomass yield advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 36 publications
10
20
0
Order By: Relevance
“…In this regard, (Odhiambo and Ariga, 2001) found that, when maize intercropped with beans in different ratios, the production increased due to reducing competition between the two species compared to the competition within specie. However, these results are in harmony with those reported by (Megawer et al, 2010) on barley intercropped with lupin and (Jalilian et al, 2017) on safflower intercropped with bitter vetch. However, fruit yield of fennel/fad., as well as seed yield and fixed oil yield per faddan of fenugreek were significantly decreased with intercropping system treatments compared to sole crop system in the first and second seasons.…”
Section: Yield Components Of Fennel and Fenugreek Plantssupporting
confidence: 92%
“…In this regard, (Odhiambo and Ariga, 2001) found that, when maize intercropped with beans in different ratios, the production increased due to reducing competition between the two species compared to the competition within specie. However, these results are in harmony with those reported by (Megawer et al, 2010) on barley intercropped with lupin and (Jalilian et al, 2017) on safflower intercropped with bitter vetch. However, fruit yield of fennel/fad., as well as seed yield and fixed oil yield per faddan of fenugreek were significantly decreased with intercropping system treatments compared to sole crop system in the first and second seasons.…”
Section: Yield Components Of Fennel and Fenugreek Plantssupporting
confidence: 92%
“…With a higher number of cowpea plants per unit area, there was better weed suppression preventing weed competition at the critical growth stages of ginger, leading to better spread of ginger rhizome. Similar result was reported by Jalilian et al [6] in inter cropping system of Bitter vetch and Saffflower where a closer row ratio of 2:2 recorded better results in comparison to 3:2, 4:2 and 5:2 row ratios.…”
Section: Ginger Fingers Per Clumpsupporting
confidence: 89%
“…Intercropping is the cultivation of two or more crops simultaneously in the same land that provides the possibility of yield benefit in accordance with sole cropping [3]. Intercropping can be performed with different planting patterns, while facilitating the use of environmental resources such as light, moisture and space efficiently to accumulate more dry matter and enhance the growth.…”
Section: Introductionmentioning
confidence: 99%